Mesoporous shell@macroporous core aluminosilicates as sustainable nanocatalysts for direct N-alkylation of amines - Sekhar, Anandakumari C. Sunil; Ashokkumar, Anumol Erumpukuthickal; Cygnet, Choorapoikayil T.; Lakshmi, Saseendranpillai Vidhya; Deepak, Francis Leonard; Vinod, Chathakudath P. (Chemnanomat, 2018)
Aluminosilicate spheres with a macroporous core and mesoporous shell (Si/Al ratio of 11) is synthesised by a sol-gel method utilizing cetyltrimethyl ammonium bromide (CTAB) as a structure directing agent in basic medium. The selective incorporation of aluminium in the silica matrix results in the formation of aluminosilicates with an overall acidity of 0.32mmol/g with interconnected pores. Direct N-alkylation reaction is a prototype of C-N bond formation reaction and meso- macroporous aluminosilicate is shown to catalyze this reaction with excellent yield. The catalyst is tested and found sustainable for five catalytic cycles even without any high temperature regeneration step.
Keywords: Aluminosilicates; macroporous; Mesoporous; N-alkylation; nanocatalysis

MnO2@Fe3O4 Magnetic Nanoparticles as Efficient and Recyclable Heterogeneous Catalyst for Benzylic sp(3) C-H Oxidation - Pandey, Akanksha M.; Agalave, Sandip G.; Vinod, Chathakudath P.; Gnanaprakasam, Boopathy (Chemistry-An Asian Journal, 2019)
Herein, we report a highly chemoselective and efficient heterogeneous MnO2@Fe3O4 MNP catalyst for the oxidation of benzylic sp(3) C-H group of ethers using TBHP as a green oxidant to afford ester derivatives in high yield under batch/continuous flow module. This catalyst was also effective for the benzylic sp(3) C-H group of methylene derivatives to furnish the ketone in high yield which can be easily integrated into continuous flow condition for scale up. The catalyst is fully characterized by spectroscopic techniques and it was found that 0.424 % MnO2@Fe3O4 catalyzes the reaction; the magnetic nanoparticles of this catalyst could be easily recovered from the reaction mixture. The recovered catalyst was recycled for twelve cycles without any loss of the catalytic activity. The advantages of MnO2@Fe3O4 MNP are its catalytic activity, easy preparation, recovery, and recyclability, gram scale synthesis with a TOF of up to 14.93 h(-1) and low metal leaching during the reaction.

Metal deficiency tuned charge transfer in intermetallic Ni2-xSn (x =0.37-0.65) enhances selective conversion of furfural to furfuryl alcohol towards the theoretical limit - Cherevotan, Arjun; Singh, Ashutosh Kumar; Yadav, Anish; Maligal-Ganesh, Raghu V.; Raj, Jithu; Pulparambil, Anu; Goud, Devender; Vinod, Chathakudath P.; Peter, Sebastian C. (Journal of Materials Chemistry A, 2025)
Heterogeneous catalysis facilitated by intermetallic nanoparticles has recently been the subject of increased scrutiny, given the enhanced selectivity and stability they bestow on many chemical reactions compared to their monometallic components. This paper explores a series of Ni-Sn (Ni2-xSn, where x = 0.65, 0.5, 0.37) intermetallic compounds supported on a high-surface-area support, SBA-15, as catalysts for the selective hydrogenation of furfural to furfuryl alcohol. Rietveld refinements of the X-ray diffraction data show catalysts with mixed intermetallic phases that assist in the catalysis. At the same time, X-ray photoelectron spectroscopy (XPS) studies and X-ray absorption studies indicate the role played by charge transfer from Sn to Ni for the catalysis. Selectivity to the desired furfuryl alcohol in all the intermetallic samples was high (>97%), but Ni1.35Sn had a relatively lower conversion than the other intermetallic compounds.